2015
DOI: 10.2310/7290.2014.00044
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Optical Imaging of Matrix Metalloproteinase Activity Detects Acute and Chronic Contact Hypersensitivity Reactions and Enables Monitoring of the Antiinflammatory Effects of N -Acetylcysteine

Abstract: The aim of this study was to determine whether the severity of contact hypersensitivity reactions (CHSRs) can be observed by noninvasive in vivo optical imaging of matrix metalloproteinase (MMP) activity and whether this is an appropriate tool for monitoring an antiinflammatory effect. Acute and chronic CHSRs were elicited by application of a 1% trinitrochlorobenzene (TNCB) solution for up to five times on the right ear of TNCB-sensitized mice. N-Acetylcysteine (NAC)-treated and sham-treated mice were monitore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 60 publications
3
17
0
Order By: Relevance
“…Two days prior to the first TNCB ear challenge, we started to add NAC continuously to the drinking water until the experiments were finished (5 mg/ml; Sigma-Aldrich, Steinheim, Germany) [20]. Sham-treated mice received normal drinking water.…”
Section: Treatment Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Two days prior to the first TNCB ear challenge, we started to add NAC continuously to the drinking water until the experiments were finished (5 mg/ml; Sigma-Aldrich, Steinheim, Germany) [20]. Sham-treated mice received normal drinking water.…”
Section: Treatment Approachmentioning
confidence: 99%
“…In this study, we focused on the temporal dynamics of ROS/RNS production and their influence on NF-κB signaling by noninvasive in vivo OI in acute and chronic TNCBinduced cutaneous contact hypersensitivity, a wellcharacterized and established experimental model for T cell-driven DTHR [19][20][21]. DTHRs are orchestrated mainly by interferon-γ-producing CD4 + (Th1) and CD8 + (Tc1) T cells [22,23] and characterized by accumulations of PMNs.…”
Section: Introductionmentioning
confidence: 99%
“…A greater number of differentially abundant proteins involved in the adaptive immune response was present in the pseudotumor group. These proteins included lactotransferrin, metalloproteinase inhibitor 1, and stromelysin‐1 (also known as matrix metalloproteinase 3), which are known to be involved in type‐IV hypersensitivity reactions . Indeed, lactotransferrin, a cell‐secreted multifunctional iron‐transport protein (also known to bind Cr 3+ ) has been shown to promote delayed‐type hypersensitivity .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, lactotransferrin, a cell‐secreted multifunctional iron‐transport protein (also known to bind Cr 3+ ) has been shown to promote delayed‐type hypersensitivity . Furthermore, metalloproteinase activity has been used to monitor contact hypersensitivity by in vivo imaging, and the injection of stromelysin‐1 in stromelysin‐1‐deficient mice has demonstrated that this protein is essential for the initiation of contact hypersensitivity . The greater abundance of these proteins in the SF of the pseudotumor group therefore suggests the presence of a type‐IV hypersensitivity reaction, which has been suspected in pseudotumor cases …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a number of commercial NIR uorescent probes have been developed for enzyme imaging in vivo. [38][39][40][41]44 In addition, new generations of NIR detectors (uorescence molecular tomography, FMT) allow the tomographic imaging of enzyme activities with high positional accuracy. 31 However, the sensitive and selective detection of enzyme activities in deeper tissues by NIR uorescent probes remains a formidable challenge because of the poor penetration and high scattering.…”
Section: Fluorescence Imagingmentioning
confidence: 99%